Skillfully collaborating chemosynthesis with GOx-enabled tumor survival microenvironment deteriorating strategy for amplified chemotherapy and enhanced tumor ablation. (19th January 2021) - Lu, Runxin; Zhou, Lin; Liu, Qijun; Wang, Siqi; Yang, Chunyan; Hai, Li; Guo, Li; Wu, Yong
Abstract : The chemosynthetic approach was skillfully combined with a GOx-enabled tumor survival microenvironment deteriorating strategy to achieve secure and satisfactory tumor ablation through multimodal synergistic starvation/oxidation/chemotherapy. Abstract : The satisfactory efficient tumor treatment and complete tumor ablation using a mono-therapeutic approach are limited owing to the tumor complexity, diversity, heterogeneity and the multiple pathways involved in tumor pathogenesis. Herein, novel, intelligent and tumor microenvironment (TME)-responsive biotin/R8 peptide co-modified nanocarriers (BRNC) loading paclitaxel (PTX)/glucose oxidase (GOx) were constructed. GOx could catalyze the oxidation of intracellular glucose to gluconic acid and poisonous H2 O2 to cause the deterioration of the tumor survival microenvironment, simultaneously achieving starvation and oxidation therapy. The acidic amplification during the GOx-mediated oxidation progress could in turn accelerate the cleavage of the acid-degradable hydrazone bond, promoting the deep penetration of nanocarriers into tumors. Even better, the aforementioned two aspects further increased the tumors' sensitivity to chemotherapeutic agents. Both in vitro and in vivo investigations indicated that the co-administration of GOx-BRNC and PTX-BRNC can remarkably improve the therapeutic efficacy and reduce side effects through the high-specific tumor targeting multimodal synergistic starvation/oxidation/chemotherapy, which would be a promising strategy for the next generation cancer therapy.